Barack Obama in his own words - Obama, Barack 1961- (Carroll & Graf, 2007)
Since delivering his keynote speech at the 2004 Democratic National Convention, Barack Obama has been hailed as the clear savior of not only the Democratic party, but of the integrity of American politics. Despite the fact that he burst onto the national scene seemingly overnight, his name recognition has grown by leaps and bounds ever since. Barack Obama in His Own Words, a book of quotes from the Illinois Senator, allows those who aren't as familiar with his politics to learn quickly where he stands on abortion, religion, AIDS, his critics, foreign policy, Iraq, the War on Terror, unemployment, gay marriage, and a host of other important issues facing America and the world.
Keywords: Obama, Barack -- Quotations; Obama, Barack -- Political and social views; Obama, Barack -- 1961-; Politik; Presidential candidates -- United States -- Quotations; Legislators -- United States -- Quotations; African American legislators -- Quotations; USA; United States -- Politics and government -- 2001- -- Quotations, maxims, etc; Zitatensammlung